A perspectiva social dos moradores atingidos pela implantação da Hidrelétrica Baixo Iguaçu - Herpich, Francine (2014)
This research sought to understand the social perspective of residents affected by the Baixo Iguaçu Hydroelectric based on theories of Young (2000; 2006) and Hannigan (1995). The field study was conducted with affected residents of the municipalities of Paraná Capitão Leonidas Marques, Capanema, Nova Prata do Iguaçu, Realeza and Planalto. The objective was to evaluate the social perspective built by affected residents of that place, in a cropped period for this research due to the deployment of the hydroelectric process being that the conflict is still ongoing. A methodology used literature review, semi-structured interviews with residents and leaders and content analysis. In the second segment, presented the context of the scenario - the theories used and the literature review on the implementation of a hydroelectric, development theories that situate this scenario, conflicts generated by different land uses and environmental licensing. In the third segment, the study was focused on the actor's research, the resident hit. Who are these residents, what are the social movements and resistance struggles. In part four, the data were presented with issues like compensation; uncertainties; losses of affected residents; community relations and participation in the process. Finally, we can conclude that the social perspective of those affected by the implementation of hydroelectric Baixo Iguaçu is constructed from feelings of anxiety and insecurity, they realizes disadvantages in the process, such as economic, psychological and social damage, mainly coming from the waiting time for the resolution of conflicts and completion of the process of implementation of hydroelectric.